ZIHNI FROM BAGHDAD AND HIS SOME OF POEMS IN POETRY COLLECTIONS - Ahmet DOĞAN (Fırat University, 2021)
Zihni from Baghdad is a poet who is estimated to have lived between in the half of the 16th century and the first quarter of the 17th  century. In sources that provide information about his life contain rather a lot limited informations. This limited informations is also a repetition of each other. The first mention of the life of Zihni from Baghdad is Ahdi from Baghdad in his biography of poets called Gülshen-i Shuara. After the Ahdi, there is no remarkable information about the Zihni from Baghdad in other sources, except for the biographys of poets of Hasan Çelebi and Esrar Dede. Zihni from Baghdad, whose real name was Abdüddelil and mentioned in the sources with expressions such as Zihni-i Baghdadi, Najafzade, Derviş Zihni-i Najafzade, Zihni-i Kadim, is a famous poet of his period. Apart from poetry, he is also an accomplished artist in calligraphy and musical sciences. Zihni from Baghdad is a good poet, according to all biographers. Among his poems are numerous muammas. Zihni from Baghdad wrote a mesnevi called Yusuf u Züleyha. There is no information that he has another work. He is said to have written numerous poems in biographical sources. However, it is not mentioned that he had a divan where he collected these poems. Examples of some poetry are included in the sources that provide information about the life of Zihni from Baghdad. These are poems written in the forms of matla, mufred, kıta, ghazal, tarji-band. The type of poem written in the form of tarjı-band is sakiname. There are also other poems in the poetry collections of the Zihni from Baghdad. In this study, the kaside, gazel and musammats found in the poetry collections of the Zihni from Baghdad will be revealed.